2015
DOI: 10.1270/jsbbs.65.103
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and genealogical analysis of grain dormancy in Japanese wheat varieties, with specific focus on <i>MOTHER OF FT AND TFL1</i> on chromosome 3A

Abstract: In the wheat (Triticum aestivum L.) cultivar ‘Zenkoujikomugi’, a single nucleotide polymorphism (SNP) in the promoter of MOTHER OF FT AND TFL1 on chromosome 3A (MFT-3A) causes an increase in the level of gene expression, resulting in strong grain dormancy. We used a DNA marker to detect the ‘Zenkoujikomugi’-type (Zen-type) SNP and examined the genotype of MFT-3A in Japanese wheat varieties, and we found that 169 of 324 varieties carry the Zen-type SNP. In Japanese commercial varieties, the frequency of the Zen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…3B, Wilcoxon rank-sum test, P = 0.72). Nakamura et al (2011) demonstrated that single nucleotide polymorphism (SNP) types of TaMFT-3A in the seven varieties showed good agreement with the order of the dormancy phenotypes: HAL, CS, AUS, and KITA have non-Zen type (nondormant) and TAMA, ZK, and OW have Zen type (dormant) (Chono et al 2015 and Supplemental Table 3). These SNP types in MFT-3A can well explain the ABA sensitivity difference among these seven cultivars.…”
Section: Phs-resistant Alleles In Wheat Varietiesmentioning
confidence: 85%
See 1 more Smart Citation
“…3B, Wilcoxon rank-sum test, P = 0.72). Nakamura et al (2011) demonstrated that single nucleotide polymorphism (SNP) types of TaMFT-3A in the seven varieties showed good agreement with the order of the dormancy phenotypes: HAL, CS, AUS, and KITA have non-Zen type (nondormant) and TAMA, ZK, and OW have Zen type (dormant) (Chono et al 2015 and Supplemental Table 3). These SNP types in MFT-3A can well explain the ABA sensitivity difference among these seven cultivars.…”
Section: Phs-resistant Alleles In Wheat Varietiesmentioning
confidence: 85%
“…R-1 genotypes of lines in this study were investigated as described by Himi et al (2011). Genotypes of Vp-1B, TaSdr-B1, MKK3, and MFT-3A, which were reported to affect PHS susceptibility, were examined according to earlier reports (Chono et al 2015, Shorinola et al 2017, Yang et al 2007, Zhang et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Collected seeds were stored at −20°C until use. Mature wheat seeds from a collection of 324 varieties previously described 19) were also used for DMACA staining.…”
Section: Methodsmentioning
confidence: 99%
“…It is assumed that the original ancestors are unrelated and characterise the genetic diversity of a set of varieties. Genealogical analysis provides estimates correlated with estimates based on marker genes (Souza and Sorrells, 1991;Cox et al 1995;Martynov et al, 2003, Chono et al, 2015. This paper presents the results of comparative analysis of genetic diversity of North-American spring wheat varieties in relation to their resistance to PHS.…”
Section: Introductionmentioning
confidence: 96%
“…This is one of the most important limiting factors influencing the production of high quality grain. Pre-harvest sprouting occurs in almost all wheat growing regions (Dobrotvorskaya and Martynov, 2013;Chono et al, 2015). Resistance to PHS is based on seed dormancy, i.e.…”
Section: Introductionmentioning
confidence: 99%